Impact of supercritical CO2 exposure time on the porosity and permeability of dry and wet shale: The influence of chemo-mechanical coupling effects. (1st May 2023) - Tian, Shifeng; Zhou, Junping; Xian, Xuefu; Gan, Quan; Yang, Kang; Zheng, Yi; Deng, Guangrong; Zhang, Fengshou
Abstract: CO2 storage in shale formation is a potential way to reduce CO2 emissions for carbon neutrality. The variation of permeability in shale triggered by CO2 -shale interaction plays an important role in CO2 sequestration. The effect of supercritical CO2 (ScCO2 ) exposure times (0, 10, 20, 30, 40 days) on the porosity and permeability evolution of dry and wet shale samples was investigated herein. Results show that the porosity and permeability of both dry shale and wet shale increased first and then decreased over exposure time, and there is an inflection point. The porosity and permeability evolution of shale is controlled by the chemical-mechanical coupling effects. The dissolution of mineral induced by ScCO2 exposure increases the porosity and permeability of shale. The mechanical weakening induced by ScCO2 exposure enhances the pores compressibility of shale, makes the porosity and permeability decrease at stressed condition. In the early stage, the chemical effect is dominant, after the time of inflection point, the mechanical weakening effect is dominant. The inflection time of wet shale is earlier than that of dry shale, indicating that the chemical effect dominant stage in wet shale is shorter than that in dry shale. This can be attributed to that the water promoted the chemical reaction and enhanced the weakening of mechanical properties, then shortened the chemical corrosion dominated stage. Our findings suggest that ScCO2 -shale interaction can contribute to the decrease in porosity and permeability of shale with the increase of ScCO2 exposure time, and hence adversely affecting the shale gas recovery and the continue injectivity of CO2 . Thus, the time dependent chemical-mechanical coupling effects should be considered in evaluating the shale gas production and CO2 storage capacity. Highlights: The impact of ScCO2 exposure time on shale porosity and permeability was obtained. The unstressed porosity of dry and wet shale increased over the ScCO2 exposure time. The stressed porosity and permeability of shale increased first and then decreased. Porosity/permeability are controlled by the chemical-mechanical coupling effects. The inflect time of porosity/permeability in wet shale is earlier than dry shale.